2007
DOI: 10.1103/physrevb.75.241304
|View full text |Cite
|
Sign up to set email alerts
|

Role of step-flow advection during electromigration-induced step bunching

Abstract: We propose a one-dimensional model based on the Burton-Cabrera-Frank equations to describe the electromigration-induced step bunching instability on vicinal surfaces. The step drift resulting from atomic evaporation and/or deposition is explicitly included in our model. A linear stability analysis reveals several stability inversions as the evaporation rate varies, while a deposition flux is shown to have a stabilizing effect.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 28 publications
4
31
0
Order By: Relevance
“…An assumed condition is |v| k where k is a typical kinetic rate of atom attachment-detachment at a step; see Remark 3.2. This condition implies that the adatom drift is slow relative to atom attachmentdetachment at step edges and is met in physical situations; see, e.g., [4,13].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An assumed condition is |v| k where k is a typical kinetic rate of atom attachment-detachment at a step; see Remark 3.2. This condition implies that the adatom drift is slow relative to atom attachmentdetachment at step edges and is met in physical situations; see, e.g., [4,13].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of the microscopic dynamics for electromigration have shown that steps can bunch or meander [4,12,16,21,36,42]. The macroscopic PDE here does capture the tendency of steps to bunch, as discussed in section 6.1.…”
Section: Limitationsmentioning
confidence: 94%
See 3 more Smart Citations